The The Comparative Study of Key Performance Ratios of Selected Indian Private Banks - Sanjana Joshi (Journal of Social Commerce, 2023)
This article is mainly based on the comparative study of India's private banks during the study period of 2017-18 to 2021-22. For the  perspective of comparative study Key performing ratios are selected and hypothesis testing is done by one way ANOVA test. The testing hypothesis is Ho hypothesis is rejected in NPM , OPM, ROCE ratio that means there is no significant difference between selected sample units, while Ho is accepted only in CASA ratio that means there is significant difference between selected sample units. And the findings of study  are HDFC Bank and KMB generate a more profit from their services  with low operating cost. It shows good operating efficiency. The performance of ICICI Bank is average during the study period, but Axis Bank's performance is not good compared with other banks.